Regional-based Integrated Healthcare Network policy in Brazil: From formulation to practice (2015)
Background Regional-based Integrated Healthcare Networks (IHNs) have been promoted in Brazil to overcome the fragmentation due to the health system decentralization to the municipal level; however, evaluations are scarce. The aim of this article is to analyse the content of IHN policies in force in Brazil, and the factors that influence policy implementation from the policymakers' perspective. Methods A two-fold, exploratory and descriptive qualitative study was carried out based on (1) content analysis of policy documents selected to meet the following criteria: legislative documents dealing with regional-based IHNs; enacted by federal government; and in force, (2) semi-structured individual interviews were conducted to a theoretical sample of policymakers at federal (eight), state (five) and municipal levels (four). Final sample size was reached by saturation of information. An inductive thematic analysis was conducted. Results The results show difficulties in the implementation of IHN policies due to weaknesses that arise from the policy design and the performance of the three levels of government. There is a lack of specificity as to the criteria and tools for configuring and financing IHNs that need to be agreed upon between involved governments. For their part, policymakers emphasize the difficulty of establishing agreements in a health system with disincentives for collaboration between municipalities. The allocation of responsibilities that are too complex for the capacity and size of the municipalities, the abandonment of essential functions such as network planning by states and the strategic role by the Ministry, the 'invasion' of competences among levels of government and high political turnover are also highlighted. Conclusions The implementation of regional-based IHN policy in Brazil is hampered by the decentralized organization of the health system to the municipal level, suggesting the need to centralize certain functions to regional structures or states and to define better the role of the government levels involved. © 2014 Published by Oxford University Press in association with The London School of Hygiene and Tropical Medicine.